Diskriminasi, Inklusi, dan Sikap Anti-Sistem pada Kalangan Muslim Sebagai Bentuk Sikap Politik Jerman - Nurfebriansyah, Ahmad Rifki; J.M., A.A.S. Mirah Mahaswari; Erviantono, Tedi (Jurnal Nawala Politika, 2022)
Muslims in Europe and North America face high levels of discrimination and hostility. This happens because of the consequences of this on the political attitudes of Muslims. Muslims personally experiencing discrimination exhibit higher anti-system tendencies: more supportive of violence, more supportive of Islamism, and less supportive of democracy and secularism. We also find that these patterns exist within a class of Muslims who believe they are “suffering themselves”, not believing that other Muslims experience similar hostility. Finally, through preliminary experiments, we found causal evidence that German Chancellor Angela Merkel's inclusive rhetoric and policies towards Muslims can help reduce this dynamic, reduce perceptions of discrimination, and in turn generate pro-system sentiment. Keywords: Discrimination; Muslim; Political